Everyday Racial Discrimination, Everyday Non-racial Discrimination, and Physical Health Among African Americans - Mouzon, Dawne M. (J Ethn Cult Divers Soc Work, 2016)
Past research has identified a link between discrimination and health outcomes among people of color. Perceptions of the cause of discrimination (racial vs. other) seem to be important for mental health; however, this relationship has not been fully examined for physical health. Using data from the National Survey of American Life, we find that, among African Americans, racial discrimination and overall discrimination regardless of attribution are associated with negative health outcomes while non-racial discrimination is not. The results suggest that racial discrimination has a unique adverse effect on physical health for African Americans that practitioners need to better understand.